The impact of digital transformation and the regulatory role of organizational culture on business model innovation in enterprises: A case study of tech startups in Vietnam - Hai, Phan Dang; Tuyet, Pham Thi (Edelweiss Applied Science and Technology, 2025)
This research addresses the critical question of how digital transformation drives business model innovation in technology startups and how organizational culture moderates this relationship—an important gap in existing studies, particularly within the context of emerging economies such as Vietnam. While previous research has examined digital transformation and innovation separately, few empirical studies have explored the interaction between digital initiatives and internal cultural factors in startup environments. The purpose of this study is to provide a deeper understanding of these dynamics and offer insights that are relevant to Vietnam’s startup ecosystem. To achieve these objectives, a quantitative research design was employed, involving the distribution of structured survey questionnaires to managers and founders of technology startups that have been operating for at least three years in Ho Chi Minh City, Da Nang, and Hanoi. A total of 327 valid responses were collected and analyzed using a three-step hierarchical regression technique to test the proposed hypotheses. The results demonstrate that digital strategy, technology application, and digital capabilities significantly enhance business model innovation. Moreover, organizational culture serves as a positive moderator, strengthening the impact of digital transformation efforts on innovation outcomes. Theoretically, this study contributes to the literature by integrating dynamic capabilities theory and organizational culture theory, offering empirical validation and extending these frameworks within an emerging market context. Practically, the findings provide actionable insights for startup managers, emphasizing the necessity of not only investing in digital technologies but also fostering a flexible, innovation-driven organizational culture.